(untitled) (Bangladesh Journal of Medical Physics, 2022)
The aim of this work is to investigate the existing shield design aspects of a semi-industrial Cobalt- 60 Gamma Irradiation Facility for 100 kCi, designed for irradiation of pharmaceutical products and daily foodstuffs as well as for research and development purposes at the Institute of Food and Radiation Biology (IFRB) of the Bangladesh Atomic Energy Commission. Earlier, the initial activity of this facility was 65 kCi and stone based reinforced concrete (SBRC) of density 2.60 g/cc and specific thicknesses were used to shield the facility for safety to operational personnel and outside public. Due to a large demand for irradiation of pharmaceutical products as well as of daily foodstuffs, IFRB has decided to increase the initial activity up to 100 kCi for this facility. For this reason, the shielding design aspects of this facility were needed to be recalculated and checked for safety. This analysis was done using the Point-kernel Shielding Code Micro-Shield 5.05 and public domain Point-kernel Shielding code QAD-CGGP2 respectively considering the radiation worker dose limit of 10 μSv/hr of the International Commission on Radiological Protection, ICRP-60, 1990. The corresponding dose limit for public at large is 0.5 μSv/hr. The calculated dose rates at different locations around the facility are far below 10 μSv/hr except in one area. This location is inside the source room. No one is allowed to enter the room when the facility is in the ON mode. However, except one location, positions outside the facility have dose rates about 3 time higher than 0.5 μSv/hr, the dose limit for public at large. Therefore, this analysis shows that the existing shield design aspects of IFRB’s Co-60 gamma source room is safe for a 100 kCi source from the viewpoint of radiation safety to operating personnel but not for public at large within proximity of the facility. Bangladesh Journal of Medical Physics Vol.15 No.1 2022 P 1-7